Education interventions in food service: are guidelines sufficient? (Research, Society and Development, 2022)
The consumption of food away from home, whether for social reasons or needs linked to the current routine and lifestyle, has contributed to the growth of food services. With the increase in the number of meals offered away from home, there is a great concern about the quality of food offered to users. With this, the objective of this article is to evaluate whether educational guidelines in service were able to modify the hygienic-sanitary and microbiological conditions of a restaurant located in the city of Petrolina, Pernambuco. To analyze the hygienic-sanitary conditions of the establishment, a checklist was used on good food handling practices based on RDC Nº216/2004 ANVISA, and classification according to RDC Nº275/2002 ANVISA. For microbiological analysis, samples of water, fried chicken and raw salad, both ready for consumption, were collected, as well as swabs on the surface of the cutting support and the blender whose surfaces come into contact with the ready-to-eat food. After 15 days of delivery of the documents and guidelines, a new visit was made to reassess the nonconformities and new microbiological analyzes were carried out. efficient in raising awareness and improving the hygienic-sanitary quality of establishments.